Communication strategies of a Malaysian politician in Tamil during the COVID-19 pandemic - Thanalachime Perumal,; Malarvizhi Sinayah,; Kumanan N Govaichelvan,; Thilagavathi Shanmuganathan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The world in general was not prepared for the coronavirus disease 2019 (COVID-19) pandemic in December 2019, which caused massive deaths. Government officials were forced to impose drastic measures to curb the spread. The Ministry of Health relied on political leaders and government agencies to help disseminate as much health information and the government policies efficiently and effectively. As these representatives or leaders belong to different ethnicities, they are more likely to understand the life circumstances, needs, strengths, and capabilities of multicultural and vulnerable communities, and would be the best people to convey the needed information. Tamils are the third largest community in Malaysia and there is not much research done on Tamil language and communication strategies during the COVID-19 pandemic. Thus, this study aims to observe on how effectively Tamil language and culture influences crisis communication. Effective communication and leadership are central to the management of pandemics and to give the public assurance in order to alleviate their fears and anxiety in having to adapt to the rapidly changing societal and economic landscape. Based on the communication strategies recommended by Hyland-Wood et al (2021), the current study focuses on how a Malaysian Indian politician, Saravanan responds, engages, and communicates with his followers. Seventeen Facebook posts in Tamil on Saravanan’s page were extracted and analysed qualitatively. The strategies utilized by Saravanan showed his resolve and effectiveness in managing crisis. This study will be useful for political leaders, community representatives, and medical practitioners in seeking equitable accessibility to quality health care and well-being of the people.